The power of heuristics in predicting fracture nonunion - Armbruster, Jonas; Steinhausen, Eva; Hackl, Simon; Reumann, Marie K.; Stengel, Dirk; Niemeyer, Frank; Reiter, Gregor; Grützner, Paul Alfred; Freischmidt, Holger (Journal of Clinical Medicine, 2025)
Background/Objectives: Although extensive research on risk factors for nonunion development has been published, clinicians frequently rely on heuristic reasoning—intuitive, experience-based decision-making—to predict nonunions. However, the accuracy of these intuitive assessments and the influence of clinician experience remain uncertain. This study aims to assess clinicians’ diagnostic accuracy in predicting nonunion, investigate the impact of experience on predictive performance, and identify patient-specific factors contributing to diagnostic errors. Methods: This retrospective, multi-center cohort study included 98 patients with surgically treated tibial shaft fractures between 2018 and 2023 from four level-one trauma centers in Germany. Fracture outcomes were classified as either nonunion (n = 20) or regular fracture healing (n = 78). Patient cases were presented to 24 clinicians. Each clinician independently assessed preoperative and postoperative biplanar X-rays and patient histories to predict fracture healing. Results: Clinicians’ sensitivity significantly improved from 50.4% to 60.2%, while specificity declined (74.0% to 70.7%) with the addition of postoperative information. No significant differences in predictive performance were observed across different levels of clinician experience. Changes in assessment after reviewing postoperative information were equally likely to be beneficial or detrimental. Certain patient factors, including obesity and smoking, influenced prediction errors. Conclusions: This study is the first to assess heuristic reasoning in nonunion prediction. The findings suggest that clinician experience does not significantly enhance diagnostic accuracy under limited-information conditions. Patients should be informed that predicting individual nonunion risk remains challenging. Larger studies are needed to explore the role of patient-specific factors and refine clinical decision-making in fracture healing prognosis.